2021
DOI: 10.1002/pmrj.12548
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury/Disorder Function, Affiliate Stigma, and Caregiver Burden in Turkey

Abstract: Background:The association among spinal cord injury and disorder (SCI/D) function, caregiver affiliate stigma, and caregiver depression and burden has not been adequately studied. In Turkey, a region with a developing healthcare infrastructure, SCI/D caregivers may have a higher responsibility of care given limited resources and may experience greater psychological distress associated with caregiving than in more developed healthcare systems. Objective: To examine whether SCI/D function, caregiver affiliate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…400 , 401 As a result, making a thorough clinical decision based on a number of clinical laboratory test signs and long-term follow-up is required rather than merely predicting the prognosis of patients based on the ASIA scale. 395 , 402 , 403 In addition, it should be noted that no studies have offered a molecular classification that can predict SCI risk and prognosis.…”
Section: Clinical Treatment and Researchmentioning
confidence: 99%
“…400 , 401 As a result, making a thorough clinical decision based on a number of clinical laboratory test signs and long-term follow-up is required rather than merely predicting the prognosis of patients based on the ASIA scale. 395 , 402 , 403 In addition, it should be noted that no studies have offered a molecular classification that can predict SCI risk and prognosis.…”
Section: Clinical Treatment and Researchmentioning
confidence: 99%
“…770, p < 0.001), family relationships (r = −0.466, p = 0.009), and overall living standards (r = −0.646, p < 0.001). Kuzu et al [ 30 ] analyzed the direct and indirect effects of depression of the caregiver of a patient with SCI, the function of the patient with SCI, the stigma on the patient’s family due to the disability, and the burden of care. In that study, it was found that caregiver burden had a negative correlation with SCI patients’ residual function (r = −0.24, p < 0.01), a positive correlation with affiliate stigma (r = 0.36, p < 0.05), and a positive correlation with caregiver depression (r = 0.51, p < 0.01) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kuzu et al [ 30 ] analyzed the direct and indirect effects of depression of the caregiver of a patient with SCI, the function of the patient with SCI, the stigma on the patient’s family due to the disability, and the burden of care. In that study, it was found that caregiver burden had a negative correlation with SCI patients’ residual function (r = −0.24, p < 0.01), a positive correlation with affiliate stigma (r = 0.36, p < 0.05), and a positive correlation with caregiver depression (r = 0.51, p < 0.01) [ 30 ]. In our study, the proportion of participants who answered that the burden of care was mainly economic was high, which is different from the study by Kuzu et al [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation